Synthesis and Evaluation of Novel Photocatalysts for Photocatalytic Reactions - Zhang, Huayang (Curtin University, 2018)
This study focuses on the design of low-dimensional (LD) photocatalysts for water oxidation in oxygen evolution reaction (OER). Through skillful approaches, such as morphological control, interface construction, defect or vacancy engineering, we developed a series of LD hybrids and examined their photo- and photoelectrochemical performances in OER. Attribute to the stable LD structure and synergistic effect of the components, the heterojunction or hierarchical materials showed enhanced charge separation, transportation, water oxidation kinetics and quantum efficiency.